PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATAKULIAH STATISTIKA PENDIDIKAN - Purnomo, Eko Andy; Dalyono, Bambang; Handayani, Sri (Jurnal Karya Pendidikan Matematika, 2018)
The curriculum and technology development hand in hand very rapidly, so it takes a concept and mechanism of ICT-based teaching and learning. The transformation process of conventional education into digital form, both in its content and its system. The progress of this technology should be utilized by the students as a provision in the classroom learning. Students are required to innovate and apply ICT in learning. Based on these things required a design and supplement learning materials so students can carry out in accordance with the demands. The one of innovation form is android-based learning media on n statistical education subject. The stages of this android system using pretest, practice working on the matter, as well as a posttest. In addition, the whole tutorial material such as SAT, RAT, concept maps and materials could be obtained by students through media-based android. The purpose of this research is to 1). know the process of developing android-based learning media is valid, 2). know the response of the students towards the implementation of the android-based learning media. The subject of this research was students of UT-UPBJJ Semarang pokjar Kendal. The development of the design and supplement learning materials used the 4-D model of Thiagarajan, Semmel Semmel and IE (define, design, develop, and disseminate). The method of data collection used interviews, observation, and question form. Based on the stages of the learning media development can be concluded 1). the android-based learning media development on educational statistics subject. The validity got 4.22 and included within the category of very valid. 2).The students ‘responses on the media-based learning android on education statistics subject had good responses. The students’ responses categories were very good 3.40.